The Influence of Budget Deficit, Government Spending, and Foreign Debt on Indonesia's Economic Growth - Indah Dwi Agustin Indah Dwi Agustin (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2025)
Objective: One of the most common things that a country uses as a reference is to know and measure the level of prosperity of its people through the level of economic growth. The purpose of this study is to investigate the impact of budget deficit variables, government spending variables, and foreign debt variables on economic growth. This study focuses on Indonesia as the research location and spans the period from 2000 to 2019. Method: This study employs quantitative calculation methods and multiple linear regression analysis (Ordinary Least Squares), which is processed using EViews software. Results: The study's findings indicate that, partially, the budget deficit and foreign debt have a significant impact on economic growth, while government spending does not have a significant effect on economic growth. While simultaneously, the three variables (budget deficit, government spending, and foreign debt) have a significant effect on economic growth. Novelty: Unlike previous studies, this study utilizes the latest and broader data, focusing on a single country, and finds differences in the results of the influence between variables.